La silla vacía y el dilema de la participación ciudadana en el Ecuador - José Luis Castro Montero (Universidad Hemisferios, 2014)
This article describes, explains and interprets through an empirical dataset analysis, how the constitutional mechanism “empty chair” operates. Initially, the conceptual and normative foundations for the institutional configuration of this mechanism are presented which in turn are forming the basis for the demonstration of its functioning among descentralized local governments (DLG) of Pichincha between 2010 and 2013. Based on the occupants’ voting dynamics, the performance of the empty chair within a setting of participatory democracy is evaluated. Both documentary analysis and semiestructured interviews are used to gather information. The conclusions suggest that highly dominant political parties among local governments may influence the occupants’ votes in the empty chair. In this context, most citizens will have low understanding of their political rights and little awareness of their responsibilities. The results also show that the “empty chair” does not necessarily strengthen the representation of civil society forces in local governments with dominant party majorities as well as in those governments where the “empty chair” is appointed in a closed way.